Balanço hídrico, crescimento e produtividade de genótipos RB de cana-de-açúcar em cultivo de sequeiro na região de Rio Largo-AL - Santos, Marcos Antonio Liodorio dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The irregular distribution of rainfall in some producing regions of cane sugar is the main cause of low agricultural productivity in northeastern Brazil. This has generated the need of genetic breeding of sugar cane for obtaining new varieties better adapted to soil and climatic adversities. Therefore, the new varieties usually need to be tested experimentally before being grown on a commercial scale in companies. Thus, in order to assess the interactions between environmental variables, the development and productivity of 10 RB genotypes sugar cane (RB92579, RB99395, RB98710, RB91514, RB961003, RB991552, RB991536, RB99383, RB9364 and RB99386) an experiment was conducted in the region of Rio Largo, Alagoas. It was conducted at the Center for Agricultural Sciences, Federal University of Alagoas. (09°28'02S; 35°49'43W; 127m). Planting was done in August (2011) in an area of 2156 m2. The statistical design was the randomized block with four replications. The first harvest was made in November 2012 and the second in December (2013). Water balance was calculated by Thornthwaite and Mather method (1977), based on data from the Laboratory of Agro meteorology and Solar Radiometry (LARAS). The year 2012 was an unusual year because the water deficiency, which typically occurs between the months of October and February in the region, expanded going the months of October through May. The water balance of culture has presented a deficit of 869 mm and an excess of 308 mm in plant-sugar cane, and a deficit of 741 mm and an excess of 790 mm in ratoon cane. Water deficiency of culture has limited the growth of genotypes mainly in ratoon cane, because the deficiency happened in sprouting and establishment, more sensitive phases of culture. On ...

A distribuição irregular da chuva em algumas regiões produtoras de cana-de-açúcar é a principal causa da baixa produtividade agrícola no Nordeste Brasileiro. Isso tem gerado a necessidade de criação de programas de melhoramento genético de cana-de-açúcar para a obtenção de novas variedades mais adaptadas às adversidades edafoclimáticas. Por isso, as novas variedades, precisam ser testadas experimentalmente antes de serem cultivadas nas empresas em escala comercial. Assim, com o objetivo de avaliar as interações entre as variáveis ambientais, o desenvolvimento e a produtividade de dez genótipos RB de cana-de-açúcar (RB92579, RB99395, RB98710, RB91514, RB961003, RB991552, RB991536, RB99383, RB9364 e RB99386), foi realizado um experimento na região de Rio Largo, Alagoas. O experimento foi conduzido no Centro de Ciências Agrárias da Universidade Federal de Alagoas (09°28'02S; 35°49'43W; 127m), o plantio foi feito em agosto de 2011 numa área com 2156 m2. Utilizou-se o delineamento estatístico em esquema fatorial de blocos casualizados com quatro repetições. A primeira colheita foi feita em novembro de 2012 e a segunda em dezembro de 2013, e o balanço hídrico foi calculado pelo método de Thornthwaite e Mather (1977), com base nos dados do Laboratório de Agrometeorologia e Radiometria Solar (LARAS). O ano de 2012 foi um ano atípico, visto que a deficiência hídrica, que normalmente ocorre entre os meses de outubro e fevereiro na região, expandiu-se de outubro até maio. O balanço hídrico da cultura apresentou déficit de 869 mm e excesso de 308 mm em cana-planta, e déficit de 741 mm e excesso hídrico de 790 mm em cana-soca. A deficiência hídrica da cultura limitou o crescimento dos genótipos principalmente em ...
Water balance, growth and productivity of rb genotypes of sugarcane in dryland farming in the region of Rio Largo - Al
Keywords: Cana-de-açúcar; Balanço hidrológico; Produtividade agrícola; Produtividade industrial; Sugar cane